Emotional stability as a professionally important quality of the future teacher (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the problem of emotional stability offuture teachers. The growing demands for the personality and behavior of theteacher, the professional competence of the specialist in the education andupbringing of the younger generation, the emotional and volitional sphere of theteacher's personality and such professionally important quality as emotionalstability. It is proved that it is precisely at the initial professionalization stagethat professional interests, values, skills are formed, as well as the formation ofpersonal qualities, both general and certain qualities that are inherent andimportant for the given professional orientation. Different approaches areconsidered concerning determination of emotional stability. The article presentsthe results of empirical research of emotional stability of future teachers.
Keywords: е моційна стійкість; педагог; первинна професіоналізація педагога; професійно важливі якості; студентський вік